Les moulins de la Martinique : un outil pédagogique - Vincent Huyghues-Belrose (Études Caribéennes)
In the collective memory of the West Indies, mills seem to be an image without human or historical context i.e. a machine deprived of its former significance it had for production of a commodity. Mills are not viewed in their former context as an important relict of the past. The purpose of the article is to give back to mills the importance that they have lost in the collective memory by reintroducing their relationship with man and the values involved in these relationships. Studying the function of machines leads to an understanding of past events, helps to interpret landscapes and especially pays tribute to the role of man.